Application of the ABC curve tool in stock management in a decoration items company - Santos, Elenilson Rivando dos; Carnaúba, Felipe Endrek Freire; Gomes, Susane de Farias (Brazilian Journal of Production Engineering, 2022)
Business competition leads organizations to seek solutions that improve their performance. The Stock Management emerges as an alternative to keep track of costs and the level of products offered by the company. This study objective to apply the ABC curve in a decoration articles company, in the wallpaper sales sector. The methodology consisted of collecting data to determine which products are most significant for the company's permanence in the market, and know which products in stock generate the highest profit, deserving attention by the manager in the acquisition of new inputs. The results show that of the 5 paper suppliers for the stock, only 40% of the items correspond to classification A, having a stock value of 76,60%, while the remaining 60% correspond to 13,83% of the value in stock for class B and 9,57% for class C. Therefore, using the ABC curve is efficient and determines which products need to be purchased in greater and lesser quantities, avoiding expenses with stock maintenance by establishing priorities during the purchase, meeting the needs of customers with items with lower value.
Keywords: ABC curve; Costs; Stock management